Psychological treatments delivered by community health workers in low-resource government health systems: effectiveness of group interpersonal psychotherapy for caregivers of children affected by nodding syndrome in Uganda - Mutamba, Byamah B.; Kane, Jeremy C.; Okello, James; Musisi, Seggane; Kohrt, Brandon A. (Psychological Medicine, 2018)
Despite increasing evidence for the benefits of psychological treatments (PTs) in low- and middle-income countries, few national health systems have adopted PTs as standard care. We aimed to evaluate the effectiveness of a group interpersonal psychotherapy (IPT-G) intervention, when delivered by lay community health workers (LCHWs) in a low-resource government health system in Uganda. The intended outcome was reduction of depression among caregivers of children with nodding syndrome, a neuropsychiatric condition with high morbidity, mortality and social stigma. A non-randomized trial design was used. Caregivers in six villages (n = 69) received treatment as usual (TAU), according to government guidelines. Caregivers in seven villages (n = 73) received TAU as well as 12 sessions of IPT-G delivered by LCHWs. Primary outcomes were caregiver and child depression assessed at 1 and 6 months post-intervention. Caregivers who received IPT-G had a significantly greater reduction in the risk of depression from baseline to 1 month [risk ratio (RR) 0.25, 95% confidence interval (CI) 0.10–0.62] and 6 months (RR 0.33, 95% CI 0.11–0.95) post-intervention compared with caregivers who received TAU. Children of caregivers who received IPT-G had significantly greater reduction in depression scores than children of TAU caregivers at 1 month (Cohen's d = 0.57, p = 0.01) and 6 months (Cohen's d = 0.54, p = 0.03). Significant effects were also observed for psychological distress, stigma and social support among caregivers. IPT-G delivered within a low-resource health system is an effective PT for common mental health problems in caregivers of children with a severe neuropsychiatric condition and has psychological benefits for the children as well. This supports national health policy initiatives to integrate PTs into primary health care services in Uganda.